Prescription of essential medication during the final hospitalization of patients with heart failure or cancer - Valentina González-Jaramillo; Monika Hagemann; Lukas Hunziker; Maud Maessen; Steffen Eychmüller (BMC Palliative Care)
Abstract Background Four medication types—opioids, benzodiazepines, anticholinergics, and antipsychotics—have been proposed as essential for patients in their final days, regardless of their primary diagnosis. These drugs are typically prescribed for individuals with cancer who are under specialized palliative care (PC+). However, it is not known whether their usage is equally common for patients with other chronic and progressive conditions, such as heart failure (HF), or for those who are not under specialized palliative care (PC-). Aim To assess the prescription frequency of each of the four medication types during the final hospitalization of patients with HF and compare it with the prescription frequency in patients with cancer (CA), considering both PC + and PC- patients in each disease group. Methods A retrospective cohort study included all patients dying in a tertiary hospital between 2016 and 2022. We created three disease groups – “HF,” “CA,” and “HF&CA” – splitting each of them into two groups, depending on whether they received PC. So there were a total of six groups – “HF PC+”, “HF PC-“, “CA PC+”, “CA PC-”, “HF&CA PC+”, and “HF&CA PC-”. Results Of the 3,874 patients, 1,921 (59%) had cancer exclusively, 371 (10%) had heart failure exclusively, and 691 (18%) had both. The median length of stay was 9 days (IQR 2–16). Within each diagnosis group, PC + patients had a higher prescription frequency for each medication type than PC- patients. For example, patients who received PC had 12 times the odds of being prescribed opioids than those who did not receive it (p < 0.05). Among the six groups, the highest prescription frequency of opioids, benzodiazepines, and anticholinergics was seen in the “HF PC+” group and the lowest in the “HF PC-” group. Antipsychotics were prescribed less frequently in the “HF PC-” and the “CA PC-” groups and were mainly prescribed in the “CA PC+” group. Conclusion Across the diagnostic groups, a notable difference in the prescription of the four medication types was observed between PC + and PC- patients. This difference was more pronounced among patients with HF (without cancer).